Stratospheric polar vortex splits and displacements in the high‐top CMIP5 climate models. Issue 4 (16th February 2016) - Seviour, William J. M.; Gray, Lesley J.; Mitchell, Daniel M.
Abstract: Sudden stratospheric warming (SSW) events can occur as either a split or a displacement of the stratospheric polar vortex. Recent observational studies have come to different conclusions about the relative impacts of these two types of SSW upon surface climate. A clearer understanding of their tropospheric impact would be beneficial for medium‐range weather forecasts and could improve understanding of the physical mechanism for stratosphere‐troposphere coupling. Here we perform the first multimodel comparison of stratospheric polar vortex splits and displacements, analyzing 13 stratosphere‐resolving models from the fifth Coupled Model Intercomparison Project (CMIP5) ensemble. We find a wide range of biases among models in both the mean state of the vortex and the frequency of vortex splits and displacements, although these biases are closely related. Consistent with observational results, almost all models show vortex splits to occur barotropically throughout the depth of the stratosphere, while vortex displacements are more baroclinic. Vortex splits show a slightly stronger North Atlantic surface signal in the month following onset. However, the most significant difference in the surface response is that vortex displacements show stronger negative pressure anomalies over Siberia. This region is shown to be colocated with differences in tropopause height, suggestive of a localized response to lower stratospheric potential vorticity anomalies. Key Points: CMIP5 models have a wide range of biases in the frequency of polar vortex splits and displacements Splits occur more barotropically than displacements in almost all models There are consistent differences in the sea level pressure response to splits and displacements